Mental Health Impacts in Argentinean College Students During COVID-19 Quarantine - López Steinmetz, Lorena Cecilia; Leyes, Candela Abigail; Dutto Florio, María Agustina; Fong, Shao Bing; López Steinmetz, Romina Lucrecia; Godoy, Juan Carlos (Frontiers in Psychiatry, 2021)
Background We aimed to: 1) analyze differences in both general (in terms of psychological well-being/discomfort, social functioning and coping, and psychological distress) and specific (depression, trait-anxiety, negative alcohol-related consequences, and suicidal risk) mental health state (MHS) in college students, residing in four different Argentinean regions (center, north, south, and the most populated) exposed to different spread-rates of the COVID-19; 2) analyze between-group differences in both general and specific MHS indicators at four quarantine sub-periods (twice prior, and twice following the first quarantine extension). Methods We used a cross-sectional design with a convenience sample including 2687 college students. Data was collected online during the Argentinean quarantine. We calculated one-way between-groups ANOVA with Tukey’s post hoc test. Results Regionally, the center and the most populated area differed in psychological well-being/discomfort and negative alcohol-related consequences, but not in the remaining MHS indicators. According to the quarantine sub-periods, there were differences in psychological well-being/discomfort, social functioning and coping, psychological distress, and negative alcohol-related consequences. Negative alcohol-related consequences were the only MHS indicator improving over time. For all of the remaining MHS indicators, we found a similar deterioration pattern in the course of time, with mean scores decreasing from the first to the second week of the quarantine pre-extensions, then increasing towards the first week of the quarantine post-extension (with some MHS indicators reaching mean scores worse than the start), and then continued to increase. Conclusion A worsened mean MHS during quarantine suggests that quarantine and its extensions contribute to negative mental health impacts.